High comorbidity and tumor proliferation predict survival of localized breast cancer patients after curative surgery: A retrospective analysis of real-world data in Finland - Hollmén, Milla; Löyttyniemi, Eliisa; Juhanoja, Eeva; Vihinen, Pia; Sundvall, Maria (Elsevier BV, 2025)
Background
The aim of this study was to analyze the characteristics of breast cancer patients and their impact on real-world treatment and survival outcomes.
Patients and methods
We conducted a retrospective study including all patients newly diagnosed with breast cancer during 2019 in the Southwest Finland. We identified 458 patients diagnosed with either localized (n = 435, 95 %) or metastatic (n = 23, 5 %) breast cancer.
Results
In localized breast cancer, the five-year overall survival (OS) was 90.9 %, while the five-year disease-free survival (DFS) was 93.5 %. In metastatic breast cancer, the five-year progression-free survival (PFS) was 13.0 % and five-year OS 34.2 %. The median PFS was 10.9 months (95 % CI 2.5–19.4 months) and median OS was 30.6 months (lower 95 % CI 6.9 months – not reached).
In the univariate analyses, the most important tumor-specific parameters predicting decreased DFS were tumor proliferation index >20 %, low estrogen receptor expression status and tumor size >2 cm. Univariate predictors for decreased OS included Eastern Cooperative Oncology Group (ECOG) performance status ≥2 and Charlson Comorbidity Index (CCI) score ≥3. In the multivariable analyses, CCI score ≥3 and high proliferation index (21–100 % vs. 0–20 %) predicted poorer DFS, while CCI score ≥3 and increased stage (stage 2 vs. 1) predicted poorer OS. The administration of post-operative radiotherapy was significant in the multivariable analyses of both DFS (HR 4.23, 95 % CI 1.85–9.67, p = 0.0006) and OS (HR 6.84, 95 % CI 3.33–14.02, p < 0.0001).
Conclusion
Our results demonstrate that careful clinical evaluation of ECOG and comorbidities, alongside well-established tumor characteristics predict patient survival in a population where overall five-year survival in breast cancer is over 90 %.